Reprogrammable metasurface design for NIR beam steering and active filtering - Bradley, Louise (My University, 2024)
Reprogrammable metasurfaces enable active modulation of light at subwavelength scales. Operating in the microwave, terahertz, and mid-infrared ranges, these metasurfaces find applications in communications, sensing, and imaging. Electrically tunable metasurfaces operating in the near-infrared (NIR) range are crucial for light detection and ranging (LiDAR) applications. Achieving a NIR reprogrammable metasurface requires individual gating of nano-antennas, emphasizing effective heat management to preserve device performance. To this end, here we propose an electrically tunable Au–vanadium dioxide (VO2) metasurface design on top of a one-dimensional Si–Al2O3 photonic crystal (PC), positioned on a SiC substrate. Each individual Au–VO2 nano-antenna is switched from an Off to ON state via Joule heating, enabling the programming of the metasurface using 1-bit (binary) control. While operating as a nearly perfect reflector at λ0 = 1.55 μm, the materials, thickness, and number of the layers in the PC are carefully chosen to ensure it acts as a thermal metamaterial. Moreover, with high optical efficiency (R ∼ 40% at λ0), appropriate thermal performance, and feasibility, the metasurface also enables broadband programmable beam steering in the 1.4 − 1.7 μm range for a wide steering angle range. This metasurface design also offers active control over NIR light transmittance, reflectance and absorptance in the wavelength range of 0.75 − 3 μm. These characteristics render the device practical for LiDAR and active filtering.
PUBLISHED
cited By 1
Keywords: reprogrammable; metasurface; beam steering; near infrared; VO2